An ethnopharmacological investigation of medicinal Salvia plants (Lamiaceae) in China - Minhui Li; Qianquan Li; Chunhong Zhang; Na Zhang; Zhanhu Cui; Luqi Huang; Peigen Xiao (Elsevier, 2013)
In China, over 40 species of the genus Salvia have been used as medicinal plants for various diseases, some for thousands of years. Recently, research has focused on the biological activities of Salvia medicinal plants used in traditional chinese medicine (TCM). However, to date a scientific survey of the genus Salvia in China has not been carried out. In this paper, we report the results of 10 field surveys of Salvia medicinal plants collected in 17 provinces including detailed information on their local names, growing environment, distribution and therapeutic effects. We also summarize the results of research on the materia medica, phytochemistry and pharmacology of some of the important Salvia medicinal plants. Our study reveals that 35 Salvia plants have been used in TCM in different regions of China, including 20 species used as Danshen to treat heart diseases, and 15 species used to treat a range of other conditions including gynecological diseases, muscular or skeletal problems, hepatitis, urological diseases, and mouth and eye conditions. It is clear that some species of Salvia L. possess significant pharmacological activity in the context of ethnopharmacological knowledge, especially in the treatment of heart disease. Further studies of the phytochemistry and pharmacology of Salvia species will no doubt improve their medical utilization and contribute to the development of new natural drugs.